Bis(pyridine-κN)bis(triphenylphosphine-κP)copper(I) tetrafluoridoborate - Healy, Peter C. (International Union of Crystallography, 2008)
The title compound, [Cu(C(5)H(5)N)(2)(C(18)H(15)P)(2)]BF(4), crystallizes as discrete [(PPh(3))(2)(py)(2)Cu](+) cations and [BF(4)](−) anions and is isostructural with the analogous perchlorate salt. The anion is located in close proximity to the pyridine ligands with weak C—H⋯F interactions apparent. The P(2)CuN(2) coordination geometry is pseudo-tetrahedral, with P—Cu—P and N—Cu—N angles of 116.02 (6) and 101.5 (2)°, respectively.